PHOTOGRAPH COLLECTION: CASTLE OF GOOD HOPE - Authors, Various (Scientia Militaria - South African Journal of Military Studies, 2012)
The Castle of Good Hope in Cape Town is South Africa's oldest and most important historical monument, so one would expect that many photographs depicting its history would be readily available, Unfortunately this is not the case and there are a number of gaps in this collection.